Anion Exchange Resins of Tri-n-butyl Ammonium Functional Groups for Dye Baths and Textile Wastewater Treatment. Issue 6 (18th September 2016) - Wawrzkiewicz, Monika; Hubicki, Zbigniew
ABSTRACT: Effectiveness of two strongly basic anion exchange resins of the gel (Dowex PSR-2) and macroporous structure (Dowex PSR-3) was compared in order to remove three hazardous dyes such as C.I. Acid Orange 7 (AO7), C.I. Reactive Black 5 (RB5), and C.I. Direct Blue 71 (DB71) contained in water and textile wastewaters. Batch adsorption experiments were carried out to analyze the effect of phase contact time, initial dye concentration, and the presence of auxiliary materials (anionic and cationic surfactants, Na2 CO3, and Na2 SO4 ). The Langmuir model better described the adsorption process of the dyes onto both resins than the Freundlich model. The monolayer adsorption capacities ( qe ) of Dowex PSR-3 were calculated as 336.4 mg/g for AO7, 317.9 mg/g for RB5, and 150.4 mg/g for DB71 at 25 ° C. Dowex PSR-2 of the gel structure is characterized by considerably lower values of qe (50.1 mg/g for AO7, 17.2 mg/g for RB5, and 9.7 mg/g for DB71). Of special importance are high values of the working ion exchange capacities of Dowex PSR-3 determined from the breakthrough curves towards AO7 and RB5 equal to 127 and 85 mg/cm 3, respectively. The pseudo second-order kinetic model described the experimental sorption data better than the pseudo first-order model. Methanol addition to the 1 M HCl and 1 M NaOH solutions improved the effectiveness of dye desorption.